Non-Hodgkin Lymphoma : Pathology, Imaging, and Current Therapy - Evens, Andrew M.; Blum, Kristie A. (Cancer Treatment and Research,, 2015)
This book provides clinical practitioners and the research community with detailed information on the diagnosis, prognosis, and treatment of non-Hodgkin lymphoma, taking into account the significant growth in knowledge including multiple therapeutic advances that have been achieved over the past 5-10 years. The work is subdivided into epidemiology, pathogenesis, pathology, imaging, and therapy of the non-Hodgkin lymphomas. The full range of therapeutic options are examined according to the major subtypes of non-Hodgkin lymphoma and the most up-to-date information is provided on current standard treatment options, including stem cell transplantation as well as new cutting-edge therapeutics.